1989
DOI: 10.1002/ar.1092240209
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of enamel gene products

Abstract: The present paper reviews the main features of amelogenin and enamelin biochemistry, molecular biology, structural and ultrastructural localization, and immunology. It also examines recent studies concerning the origin, chemical characterization, suggested role, and participation of these two major classes of extracellular developing enamel matrix proteins in the complex process of "matrix-mediated" mineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 150 publications
3
58
0
1
Order By: Relevance
“…Control experiments using antigen-absorbed antiserum resulted in no specific staining. Although we have no immunochemical data on the specificity of this antiserum against human enamel proteins, previous immunochemical and immunohistochemical studies have demonstrated an extensive cross-reactivity between amelogenins of a variety of mammalian species (HEROLD et al, 1979;ZEICHNER-DAVID et al, 1987;DEUTSCH, 1989). Sequencing studies have shown that there is a high degree of sequence conservation in amelogenins derived from bovine, porcine and human specimens (FUKAE et al, 1980;FINCHAM et al, 1983;TAKAGI et al, 1984).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Control experiments using antigen-absorbed antiserum resulted in no specific staining. Although we have no immunochemical data on the specificity of this antiserum against human enamel proteins, previous immunochemical and immunohistochemical studies have demonstrated an extensive cross-reactivity between amelogenins of a variety of mammalian species (HEROLD et al, 1979;ZEICHNER-DAVID et al, 1987;DEUTSCH, 1989). Sequencing studies have shown that there is a high degree of sequence conservation in amelogenins derived from bovine, porcine and human specimens (FUKAE et al, 1980;FINCHAM et al, 1983;TAKAGI et al, 1984).…”
Section: Discussionmentioning
confidence: 89%
“…Although several biochemical and immunochemical reports have dealt with enamel proteins of the human tooth germ (FINCHAM, 1980;ROBINSON et al, 1981;DEUTSCH et al, 1983DEUTSCH et al, , 1984FINCHAM et al, 1983;ZEICHNER-DAVID et al, 1987), no report has discussed the immunocytochemical localization of enamel proteins, except for a brief description by DEUTSCH (1989) at the light microscopic level. In the present study, we investigated the ultrastructural localization of amelogenin-like immunoreactivity in the deciduous tooth germ of the human fetus.…”
Section: Discussionmentioning
confidence: 99%
“…They performed a phylogenetic analysis based on the literature data including 10 amelogenin sequences (8 mammals, 1 crocodile, and 1 amphibian). Such a question is based on the assumption that the amelogenin proteins certainly play an important role in enamel deposition and maturation (Deutsch 1989;Diekwisch et al 1993). Mathur and Polly (2000) concluded that amelogenin evolution slows as enamel complexity increases, probably because selective constraints on amelogenin increase as enamel complexity increases.…”
Section: Insertion Of Triplet Repeats and Amino Acid Deletionsmentioning
confidence: 99%
“…During development of tooth enamel, ameloblast cells within the enamel organ secrete an organic matrix comprising primarily proteins called amelogenins and enamelins (tuft proteins) (Eastoe, 1979;Deutsch, 1989;Limeback, 1991). Amelogenins constitute approximately 90% of the enamel matrix protein and are relatively easy to extract from developing teeth using 4 M guanidine hydrochloride, while the more acidic enamelins are thought to adhere tightly to enamel mineral crystals, which must be dissolved with 0.5 M EDTA in order for the guanidine extraction to be efficient (Termine et al, 1980).…”
Section: Introductionmentioning
confidence: 99%